PENGGUNAAN VIDEO PEMBELAJARAN UNTUK MENINGKATKAN HASIL BELAJAR SENI RUPA DI SEKOLAH MENENGAH PERTAMA - Handriani Jusmita; Suib Awrus (Universitas Negeri Padang, 2020)
So that students get good learning results, teachers are required to always be creative and have variations in teaching so tha students can receive lessons, the teachers has not used the right media, many teachers still use blackboard media, and worksheets so that students find it difficult in understanding conceptual material and skills such as learning fine arts. Based on a search on google scholar found many studies on the use of instructional video media to improve learning outcomes, for that the writer examines the use of these instructional videos. Writing scientific articles aims to find out how appropriate the use of instructional videos on learning fine arts, how to use it, and whether the use of these instructional videos can improve learning outcomes. The method used in this research is library research, the data obtainedournals related to the comes from journals related to the variables used, the audthor got the journal from google scholar. After reviewing 16 reference journals obtained the average learning outcomes after using instructional video media amounting to 78.50. the average learning outcomes prove that the use of instructional video media can improve learning outcomes.Keywords: learning video media, learning outcomes, study of literature